Competence Development in Fixed-term Employment - Gesa Münchhausen (Adult Education Research Conference, 2011)
A German research project seeks to provide answers on how fixed-term employment affects the development of occupational competences. The objective is to compare the impact of this form of employment on competence acquisition by fixed-term employees and employees in “normal” working relationships from a subjective angle. Criteria for comparison are: scope for activity, task diversity, complexity of work, career opportunities, participation in formal continuing train- ing, social support and integration, decision-making powers, information offer- ings as well as job satisfaction. The project uses qualitative and quantitative re- search methods - that are a guided qualitative survey on the one hand and a repre- sentative survey of the workforce on the other one. Main findings are to be pre- sented.
Keywords: Competence development; atypical employment; continuing vocational training; lifelong learning